2006
DOI: 10.1097/01.ico.0000178725.04070.87
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Healing of Vernal Shield Ulcer After Surgical Debridement

Abstract: Corneal shield ulcers and plaques are rare but serious complications of vernal keratoconjunctivitis, which may be unresponsive to standard medical therapy. Surgical debridement is a fast and effective procedure yielding rapid healing of the ulcer and minimizing complications, such as infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
1
13
0
2
Order By: Relevance
“…Debridement of ulcer base, surgical removal of plaque or excimer laser phototherapeutic keratectomy helps in early re-epithelialization of vernal shield ulcer refractory to medical treatment. (Cameron et al 1995b;Solomon et al 2004;Ozbek et al 2006). Amniotic membrane implantation leads to complete re-epithelialization of persistent corneal epithelial defects and vernal plaques recalcitrant to conventional medical treatment (Rouher et al 2004;Pelegrin et al 2008).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Debridement of ulcer base, surgical removal of plaque or excimer laser phototherapeutic keratectomy helps in early re-epithelialization of vernal shield ulcer refractory to medical treatment. (Cameron et al 1995b;Solomon et al 2004;Ozbek et al 2006). Amniotic membrane implantation leads to complete re-epithelialization of persistent corneal epithelial defects and vernal plaques recalcitrant to conventional medical treatment (Rouher et al 2004;Pelegrin et al 2008).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Elevated plaques are grade 3 shield ulcers, which respond best to surgical therapy. Topical formulations of corticosteroids, antihistamines and artificial tears, surgical excision of giant papillae with 6 or without mitomycin, supratarsal steroid injection, 7 surgical debridement of ulcer base, 8 amniotic membrane transplant, 9 autologous conjunctival graft, excimer laser phototherapeutic keratectomy and CO 2 ‐assisted removal of giant papillae 10 have all been tried with varying degrees of success in the treatment of shield ulcer with or without plaque.…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, the giant papillae can occasionally be surgically removed in conjunction with an autologous conjunctival graft or AMT, which can also accelerate the healing process of a shield ulcer. 30,31 Most patients with AKC respond well to the abovementioned topical therapies. In a few studies, authors have reported the use of systemic immunosuppressant therapy, including oral cyclosporine and tacrolimus, in patients with refractory AKC, and corticosteroid, methotrexate, azathioprine, and mycophenolate mofetil for patients with recalcitrant AD.…”
Section: S473mentioning
confidence: 99%